The Representation of Peace Values in the ELT Textbook for Senior High School Students - Jasmine Choirun Nisa (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The countless turmoil of conflicts and violence have occurred in the shape of human life in society. As a consequence of this social phenomenon, the worst part of this state of disarray and confusion is influencing young people’s minds to undertake violent and aggressive actions toward themselves, other people, and their surroundings (Balasooriya, 2001; Jahan & Khan, 2017; Yahaya et al., 2020). Thus, the nurturing of peace values among the students becomes an urgent issue that needs to be addressed (Balasooriya, 2001). Integrating peace values in the educational scope can be one of the effective ways to cope with the current issue. This is because education can be a medium for conveying peace values by ways of predisposing students’ minds to implement noble characters and attitudes in real life which assist them in facing present and future challenges (Bashir & Akbar, 2021; Hasan & Juhannis, 2024; Khan, 2014). Therefore, the integration of peace values can be strengthened through textbooks, since textbook is a medium to deliver universal values (Gebregeorgis, 2016). As a result, the textbook is expected to promote peace values through the textbook artifacts potentially. This study has the purpose of examining the representation of peace values represented through the visual artifacts with the accompanying verbal text contained in the emancipated curriculum textbook. The object of this study is the ELT textbook published by The Indonesian Ministry of Education, Culture, Research and Technology, entitled ‘Bahasa Inggris English for Change’ for the eleventh grade of senior high school students. The textbook was written by native Indonesian authors and released in 2022. It contains 266 pages with 5 chapters used as a medium in the teaching-learning process at schools in Indonesia where English is used as a foreign language.The data collected in this study was gained from document analysis (Bowen, 2009) which contains systematic procedures to observe and evaluate printed or electronic documents. Then, the data were analyzed using the Multimodality framework from Kress & Leeuwen (2006) to reveal the hidden meanings within the visual artifacts (pictures, photographs, and diagram trees) accompanied by the verbal text (pertains to written text) in the target textbook. Thus, the results of the analysis show that the two categories of peace values were represented in the textbook which includes two pictures and four photographs with the verbal texts represented peace with nature, and two pictures with the verbal texts represented inner peace.
Reupload File Repository 11 Juni 2026_Yudi Validasi repository 11 Juni 2026_Dila/Firly
Keywords: Representation of Peace Values; ELT Textbook; Senior High School Students